Hadoop : data processing and modelling : unlock the power of your data with Hadoop 2.X ecosystem and its data warehousing techniques across large data sets /: data processing and modelling : unlock the power of your data with Hadoop 2.X ecosystem and its data warehousing techniques across large data sets. (2016) - Turkington, Garry; Deshpande, Tanmay; Karanth, Sandeep
No abstract available